Clustering‐Triggered Emission of Nonconjugated Polyacrylonitrile. Issue 47 (8th September 2016) - Zhou, Qing; Cao, Boyu; Zhu, Chenxuan; Xu, Si; Gong, Yongyang; Yuan, Wang Zhang; Zhang, Yongming
Abstract : Intrinsic emission from nonconjugated polymers has attracted considerable attention owing to its fundamental importance and intensive applications in diverse fields. The emission mechanism, however, is still in debate. Herein, nonconjugated polyacrylonitrile (PAN) molecules are found to be virtually nonluminescent in dilute solutions, while being highly emissive when concentrated or aggregated as nanosuspensions, solid powders, and films, exhibiting distinct aggregation‐induced emission (AIE) characteristics. Moreover, triplet emissions of delayed fluorescence and room temperature phosphorescence are detected from the solid powders. Such unique emission of nonconjugated PAN is ascribed to the formation of cyano clusters, which act as the exact chromophores. In these clusters, through space electronic interactions, namely overlap of π and lone pair (n) electrons among cyano groups extend the conjugation and meanwhile rigidify the molecular conformations, thus offering remarkable emission upon irradiation. The AIE phenomenon can also be well rationalized by the formation of cyano clusters together with conformation rigidification. And the triplet emissions shall be originated from the n–π* transition owing to the presence of lone pairs. It is believed that such clustering‐triggered emission mechanism is instructive for further development of unorthodox luminogens. Abstract : Together we shine: clustering‐triggered emission is found in nonconjugated polyacrylonitrile (PAN), in which cyano clusters with electron overlap rather than isolated groups are essential to the light emission. While molecularly dissolved in dilute solution, PAN molecules are virtually nonluminescent. They become emissive, however, when concentrated or aggregated, owing to the clustering of cyano units and conformation rigidification.